Incorporating peer feedback in academic writing: a systematic review of benefits and challenges - Wei, Yuzhu; Liu, Donghong (Frontiers in Psychology, 2024)
Academic writing is paramount to students’ academic success in higher education. Given the widely acknowledged benefits of peer feedback in diverse learning contexts, such as fostering a positive psychological mindset, there has been a growing interest in applying this approach to facilitate the development of academic writing. This study is launched to examine the primary features and findings of the studies that have investigated the benefits and challenges of the utilization of peer feedback in academic writing development. The methodology of this study incorporates a rigorous literature search methodology, encompassing database search, reference search, and manual search, which is subsequently followed by a content analysis of the selected studies. With the guidance of PRISMA 2020, a total of 60 related articles, spanning the period from 2014 to 2024, are selected through title screening, abstract screening and content screening, adhering to strict inclusion and exclusion criteria. The findings of this study reveal a growing global interest in peer feedback in academic writing, and highlight the need for future research on masters’/doctoral students and quantitative approaches to deepen understanding of its effects. Moreover, 16 distinct benefits of peer feedback in the academic writing context were delineated and subsequently categorized into five categories: affective benefits, cognitive benefits, behavioral benefits, social benefits, and meta-cognitive benefits. Furthermore, an analysis of the implementation challenges revealed 13 types of obstacles, which were traced to three primary sources: challenges originating from feedback receivers, those posed by feedback providers, and those stemming from the peer feedback settings. Based on these findings, several pedagogical and future research suggestions are proffered to guide both the practitioners and researchers.